Clouds over Tianshan : essays on social disturbance in Xinjiang in the 1940s - Wang, David (NIAS report, 1999)
"The 1940s saw the outbreak of the so-called Yili rebellion, which led to the collapse of Chinese state authority over a wide area of Xinjiang in the chaotic years of the later 1940s. Much of the story of this rebellion has been told before but what is especially interesting here is Wang's demonstration that the rebellion was not an internal Chinese matter; rather it was very much an international affair. Here he looks not just at the ethnic and religious dimensions, which of course had many international ramifications. But what is not generally recognised is that, politically, there were three external actors in the affair: the Chinese Nationalist government, the Chinese communists and (especially) the Soviets. The dynamics between these three actors, as World War II came to an end and the Chinese civil war gathered pace, had a major impact on the course of events in Xinjiang between 1944 and 1949."--BOOK JACKET.